Interaction between a novel intronic IVS3+ 172 variant and N29I mutation in PRSS1 gene is associated with pancreatitis in a Malaysian Chinese family - Chua, K.H.; Puah, S.M.; Chew, C.H.; Wong, C.H.; Goh, K.L. (2011)
BACKGROUND/AIMS: Hereditary pancreatitis (HP) is a very rare form of early-onset chronic pancreatitis, which usually begins in childhood with a variable spectrum of severity of disease. HP is commonly caused by variants/mutations in the PRSS1 gene as reported in many studies. Therefore, in this study, we aimed to investigate the possible association of PRSS1 gene variants/mutations in a Malaysian Chinese family with HP. METHODS: Genomic DNA of the 6 family members was extracted, amplified using polymerase chain reaction and the entire PRSS1 gene was analyzed via sequencing. RESULTS: PRSS1 gene sequencing results revealed two variants/mutations in this study. The results show that all the subjects (patients) inherited an intronic SNP IVS3+172 variant, together with a p.N29I mutation except for subjects 3 and 4 who are normal. CONCLUSION: We believe that interaction between the novel IVS3+172 intronic variant and p.N29I mutation in the PRSS1 gene is associated with HP in this Malaysian Chinese family.